MODEL BANK JELANTAH BERBASIS MASYARAKAT DI KELURAHAN BANGUNHARJO: SOLUSI PENGELOLAAN LIMBAH DAN PENINGKATAN EKONOMI - Mutoharoh Mutoharoh; Naila Najihah; Zainal Alim Adiwijaya (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The initiation of Used Cooking Oil (UCO) Bank is a community-based mentoring program for managing used cooking oil for female community in Bangunharjo Village, Semarang. Bangunharjo is one of the densely populated areas in the centre of Semarang City, with most residents working as food seller who potentially contribute to produce a significant cooking oil waste in addition to other household activities. This cooking oil bank was initiated to increase public awareness of maintaining environment and become an opportunity to change waste into more economic value. By implementing the Participatory Learning and Action (PLA) method, this program is implemented with the preparation, practice, and evaluation stages. The output of this program is the establishment of a Used Cooking Oil Bank in the partner area. The evaluation results show that the initiated bank went well in the first six months by producing income for both residents and the organization. During the implementation, no significant obstacles hindered the achievement of the goals. This initiation can be developed in various other areas by ensuring the appointment of the proper coordinator with the full support of the regional board of Family Welfare and Empowerment Organization (PKK).